MENGKAJI KUALITAS PELAYANAN PUBLIK BUMN: STUDI KASUS LAYANAN PASANG BARU LISTRIK DI PT PLN PERSERO - Nurul Izzati; Dadan Kurniansyah; Mochamad Faizal Rizki (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2026)
This research aims to determine the quality of public services for new electricity installation at PT PLN (Persero) ULP Haurgeulis. Public service issues became a significant concern after the 1998 Reform, which demanded clean, professional, and responsive governance. Electricity, as a basic need in the digital age, places PT PLN (Persero) in a vital role in fulfilling the rights of the community. However, at ULP Haurgeulis, delays in new installation services are still found due to the imbalance between the wide geographical coverage and limited human resources. This research uses the SERVQUAL public service quality theory with five dimensions: tangibility, reliability, responsiveness, assurance, and empathy. Data collection techniques were carried out thru interviews, policy document studies, field observations, and searches of mass media and social media articles. Data analysis was performed using pattern matching techniques by comparing empirical findings with expected patterns. The research results show that the four SERVQUAL dimensions, namely reliability, responsiveness, assurance, and empathy, are already in the optimal category. However, the tangibility dimension, particularly in terms of human resources, is still not optimal due to limitations in administrative staff, which leads to delays in service. The conclusion of this study is that the quality of new electricity installation services at ULP Haurgeulis is generally good, but increasing the number and capacity of human resources is still needed to maximize service. The implications of this research policy emphasize the need to strengthen and organize human resources within PT PLN (Persero)'s regional service units to improve the effectiveness of new electricity installation services.